Pengaruh Motivasi Kerja Dan Pengalaman Kerja Terhadap Kualitas Kerja Guru Pada SMKN 1 Bukit Sundi - Trivira Melenia; Rasidah Nasrah; Nurhayati Nurhayati (Lembaga Pengembangan Kinerja Dosen, 2023)
.This study aims to see the Effect of Work Motivation and Work Experience on the Quality of Teacher Work at Smkn 1 Bukit Sundi. the type of research used is correlative descriptive research. Descriptive correlatives are a research method that aims to see the relationship between two or more variables. The influencing variable is an independent variable (X), while the variable affected by the independent variable is called the dependent variable (Y). Based on the results of the study obtained the double linear regression equation is Y = 45.312 -0.057X1 +0.100X2 +e The value of the constant is 45.312. The results of the study determined by Rsquare were 0.012 or 1.2%. H1 was received with a calculated value of -0.267 <2,051 and a signification value greater than 0.05 (0.791 > 0.05), H2 was received with a calculated value of 0.525 < a table of 2.051 and a signification value greater than 0.05 (0.604 > 0.05). H3 did not have a significant and simultaneous influence together on the teacher work quality with a calculated F value of 0.160 < Ftabel of 3.34 and a signification value of 0.853 > 0.05.